DIFFICULTIES IN SCREENING FOR CERVICAL CANCER IN INDIGENOUS WOMEN: AN INTEGRATIVE REVIEW - Costa Duarte, Tamires; Claudino de Jesus Carvalho, Matheus; Mikaela Moreira de Oliveira, Ingrid; Taylor de Almeida Pinheiro Pires, Hudson; Cesar Pereira da Silva, Julio; Aparecido Nascimento Silva, Raylton; Gouvea do Carmo e Silva, Iago; da Silva Viana, Yara; Claudino de Jesus Carvalho, Gabriel; Daniel Zanoni, Rodrigo (Health and Society, 2023)
Cervical cancer, also known as cervical cancer, is a malignant tumor that develops in the cervix, mainly caused by persistent infection with some types of Human Papillomavirus, present among the female population and responsible for high rates of morbidity and mortality. mortality in the world. In indigenous women, cervical cancer can be more lethal due to low adherence to health services, as well as periodic Pap smears. This happens due to the scarcity of information that consequently generates the lack of knowledge of this population about the importance of the cytological examination. Therefore, knowing the relevance of this theme, this study was developed with the aim of identifying, in the literature, the factors that make it difficult for health professionals to carry out the preventive examination for the screening of cervical cancer in indigenous women. This is an integrative review carried out in scientific data sources: Scientific Electronic Online Library (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Nursing Database (BDENF). From the analysis of the literature, several aspects were evidenced that influence the evasion of indigenous women from health systems. Their customs and traditions are factors that interfere in health promotion. However, the key to reversing this scenario are health strategies with educational actions carried out by trained professionals and by the Basic Health Unit. The present review showed, through the scientific literature, the importance of incorporating health education, as well as the need to expand and qualify health care and promotion actions aimed at indigenous women and their ethnic-cultural particularities. Therefore, it is suggested that for such an achievement, informative adherence is essential for cervical cancer screening.